1992
DOI: 10.1128/jb.174.5.1462-1477.1992
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequences of the tail fiber genes of bacteriophage P2: evidence for horizontal transfer of tail fiber genes among unrelated bacteriophages

Abstract: We have determined the DNA sequence of the bacteriophage P2 tail genes G and H, which code for polypeptides of 175 and 669 residues, respectively. Gene H probably codes for the distal part of the P2 tail fiber, since the deduced sequence of its product contains regions similar to tail fiber proteins from phages Mu, P1, lambda, K3, and T2. The similarities of the carboxy-terminal portions of the P2, Mu, ann P1 tail fiber proteins may explain the observation that these phages in general have the same host range.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
139
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(148 citation statements)
references
References 83 publications
8
139
0
1
Order By: Relevance
“…The example of the dCTPase genes shows that in this situation, horizontal gene transfer can generate mosaic sequence divergence within essential genes, in turn, establishing species barriers. Similar mosaic arrangements in other genes of the T-even (69,71) and other phages (67) are also most readily explained by the mechanism illustrated in Fig. 3.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The example of the dCTPase genes shows that in this situation, horizontal gene transfer can generate mosaic sequence divergence within essential genes, in turn, establishing species barriers. Similar mosaic arrangements in other genes of the T-even (69,71) and other phages (67) are also most readily explained by the mechanism illustrated in Fig. 3.…”
Section: Discussionmentioning
confidence: 62%
“…Illegitimate site-specific recombination or transposition have been proposed to exchange entire gene modules of related functions (66). However, gene segments can also be exchanged or added (67)(68)(69)(70)(71). We have suggested that a combination of join-copy and join-cut-copy pathways, together with heteroduplex repair (Fig.…”
Section: Mutagenic and Evolutionary Potential Of Homologous Recombinamentioning
confidence: 99%
“…In the 'tail fibre, host recognition' module, ORF 45 contains a domain of the Phage tail fibre adhesin Gp38 Pfam family (Table 1). In T2-like phages, gp38 is responsible for recognition of host cell receptors (Haggard-Ljungquist et al, 1992); it is thus considered to be a critical factor for change and is one of the most rapidly evolving components of a phage-host system.…”
Section: Genome Features and Annotationsmentioning
confidence: 99%
“…58 Gene H encodes the tail fiber protein, and gene G is required for tail fiber assembly. 59 The tail genes F I , F II , E, T, U and D comprise a single transcription unit. 50,52 Gene F I encodes the tail sheath, and F II encodes the tail tube.…”
Section: The Lysis Genesmentioning
confidence: 99%